Pengenalan Penguatan Kelembagaan Pada UMKM Bank Sampah Lestari 25 - Zackharia Rialmi; Ranila Suciati; Siti Hidayati; Ranti Nugraheni (Indonesian Journal of Society Engagement, 2021)
Institutional strengthening in the form of establishing an organizational structure model, drafting job descriptions and handling conflicts are very important issues today. The need for institutional strengthening is needed not only in large organizations but also very much needed by small organizations such as MSMEs (Micro, Small, and Medium Enterprises). The Garbage Bank is a type of investment from the sale of community waste that is not cashed directly but is recorded as personal savings. The Sustainable Waste Bank, which was established by a community of environmental care residents at Perum Taman Banten Lestari, has experienced ups and downs in its organizational journey, institutional strengthening is expected to be one of the supporting tools so that this organization can survive and grow in the future. From the results of the implementation of this institutional strengthening activity, results were obtained in the form of a more introduction to the importance of making a clear organizational structure and preparation of job descriptions so that there is no overlapping in the implementation of duties and authorities within the organization. Abstrak Penguatan kelembagaan berupa penetapan model struktur organisasi, penyusunan job description dan handling conflict menjadi isu yang sangat penting dewasa ini. Kebutuhan akan penguatan kelembagaan diperlukan tidak hanya di organisasi besar tetapi juga sangat diperlukan oleh organisasi kecil seperti UMKM (Usaha Mikro, Kecil, dan Menengah). Bank Sampah merupakan jenis investasi dari penjualan sampah masyarakat yang tidak secara langsung diuangkan akan tetapi dicatat sebagai tabungan pribadi. Bank Sampah Lestari yang didirikan komunitas warga peduli lingkungan hidup di Perum Taman Banten Lestari ini mengalami pasang surut di dalam perjalanan organisasinya, penguatan kelembagaan diharapkan menjadi salah satu tools yang mendukung agar organisasi ini bisa survive dan semakin berkembang ke depannya. Dari hasil pelaksanaan kegiatan penguatan kelembagaan ini didapatkan hasil berupa pengenalan lebih akan pentingnya pembuatan struktur organisasi yang jelas, dan penyusunan job description sehingga tidak terjadi tumpang tindih pelaksanaan tugas dan wewenang di dalam organisasi. Kata Kunci: penguatan kelembagaan; struktur organisasi; job description; umkm bank sampah